Assessment of correlations between sildenafil use and comorbidities and lifestyle factors using wastewater-based epidemiology. (30th June 2022) - Shao, Xue-Ting; Zhang, Pei-Yao; Liu, Si-Yu; Lin, Jian-Guo; Tan, Dong-Qin; Wang, De-Gao
Highlights: Sildenafil use accounted for 13.3% of licit use in China. Sildenafil use was significantly higher in North China than South China. Sildenafil use was positively correlated with allopurinol and hydrochlorothiazide. Smoking and drinking increase the consumption of sildenafil. Abstract: Sildenafil (SIL) is widely used to treat erectile dysfunction. Information on its consumption and the factors influencing its use is limited in China. In this study, we sampled composite influent wastewater samples from 33 Chinese cities and analyzed SIL using liquid chromatography-tandem mass spectrometry. SIL consumption was estimated using wastewater-based epidemiology (WBE) and ranged from 10.6 mg/d/1000 people to 132 mg/d/1000 people, with a mean of 53 mg/d/1000 people. Prescription sales (3570 kg) accounted for 13.3% of the estimated SIL use (26842 kg) in 2018, thereby implying that SIL illicit use was greater than prescription use in China. Some regional differences were observed in SIL use, which was significantly higher in North China than South China ( p  < 0.05), thereby reflecting that the prevalence of SIL was affected by differences in lifestyle and socioeconomic factors. We found significant positive correlations between SIL use and consumption of allopurinol, hydrochlorothiazide, nicotine, and alcohol, thereby suggesting that the prevalence of SIL was associated with the prevalence of gout, hypertension, smoking, and drinking. Moreover, age structures, internet use, and marriage rates were positively correlated with SIL use, whereas the unemployment rate was negatively correlated with SIL use. Our study demonstrates that WBE is valuable for medical research to investigate licit and illicit drug use and to assess the underlying associations of different chemical uses. Graphical abstract: Image, graphical abstract